2011
DOI: 10.1371/journal.pgen.1001291
|View full text |Cite
|
Sign up to set email alerts
|

CSP and Takeout Genes Modulate the Switch between Attraction and Repulsion during Behavioral Phase Change in the Migratory Locust

Abstract: Behavioral plasticity is the most striking trait in locust phase transition. However, the genetic basis for behavioral plasticity in locusts is largely unknown. To unravel the molecular mechanisms underlying the behavioral phase change in the migratory locust Locusta migratoria, the gene expression patterns over the time courses of solitarization and gregarization were compared by oligonucleotide microarray analysis. Data analysis revealed that several gene categories relevant to peripheral olfactory perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
305
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 232 publications
(316 citation statements)
references
References 51 publications
8
305
2
1
Order By: Relevance
“…In addition, it was found that fourth instar locusts displayed the most divergence between polymorphic states. This was confirmed by micro-array studies, which illustrated that the top pathways affected in gregarious nymphs at fourth stage were involved in general metabolism and catecholamine biosynthesis (Ma et al, 2011).…”
Section: Transcriptomicsmentioning
confidence: 57%
See 4 more Smart Citations
“…In addition, it was found that fourth instar locusts displayed the most divergence between polymorphic states. This was confirmed by micro-array studies, which illustrated that the top pathways affected in gregarious nymphs at fourth stage were involved in general metabolism and catecholamine biosynthesis (Ma et al, 2011).…”
Section: Transcriptomicsmentioning
confidence: 57%
“…In addition, it was found that fourth instar locusts displayed the most divergence between polymorphic states. This was confirmed by micro-array studies, which illustrated that the top pathways affected in gregarious nymphs at fourth stage were involved in general metabolism and catecholamine biosynthesis (Ma et al, 2011).Another micro-array study on fourth instar migratory locusts during phase transition revealed differential expression in chemosensory proteins and takeout proteins (Guo et al, 2011). Genes of these families were found to be highly expressed in peripheral tissues (sensilla, antennae, labial palps, wings and hindlegs) but not internal tissues.…”
mentioning
confidence: 80%
See 3 more Smart Citations